MEAT SHOP (CIPEEX, 2025)
The MeatShop software aims to modernize the butcher industry by streamlining inventory management and order reception, enhancing communication between customers and suppliers. The application offers features such as product catalog, order tracking, scheduling, and purchase history, focusing on improving customer experience and operational efficiency. The development process followed agile methodologies, including Scrum and Kanban, ensuring organized progress. Initially, market research and statistical analysis were conducted to identify user needs. Based on these insights, a Minimum Viable Product (MVP) was created, and the database and class design are currently in development. Additionally, the user interface and experience (UI/UX) are being redesigned to optimize the MVP for near-term use, with plans to implement additional features at a later stage. Payment and delivery processes remain the responsibility of the butcher shop, allowing greater flexibility for businesses. The results show that the MeatShop significantly benefits the sector by reducing communication issues, speeding up the ordering process, and increasing customer satisfaction. This tool has the potential to streamline daily operations, boost sales, and reach a broader customer base.
Keywords: butcher shop; orders; stock; innovation